The Use of English Language Speech Assistant (ELSA) Speak Application to Improve Pronunciation - Alwin, Wina Rizqiyana; Konder Manurung; Desrin Lebagi; Mukrim, Mukrim (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research aimed to investigate the effectiveness of English Language Speech Assistant (ELSA) speak application is effective in improving students’ pronunciation at SMP Negeri 1 Sirenja. The primary research question is whether or not the use of English Language Speech Assistant (Elsa) speak application is effective in improving students’ pronunciation. The research used a quasi-experimental design with an applied non-equivalent control group design. The research used a purposive sampling technique and took a sample of 57 students. The subject of this research was the eighth-grade students at SMP Negeri 1 Sirenja class A and B. B class was an experimental group while A class was a control group. The research instrument was a pronunciation test that was given as a pre-test and post-test. The data collected was analyzed by using descriptive statistics and inferential analysis using SPSS 22 version program. Based on the result of the hypothesis test (t-test), the value from the data analysis that has been conducted shows a significance value of 0.000<0,05. In addition, the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. In conclusion, the use of English Language Speech Assistant (ELSA) speak application is effective in improving students’ pronunciation.